Perspective of new technical provisions for buildings in the context of defects of current regulation - Kamil Kułaga (Acta Scientiarum Polonorum. Architectura)
The article portrays the circumstances of the obligation to issue new technical provisions and, based on the example of the current Regulation on the technical conditions to be met by buildings and their location, it presents selected defects of this regulation and certain tasks facing the lawmaker who is to design a new regulation. The general negative assessment of the quality of the existing provisions, which is mainly influenced by legislative weaknesses, was reasoned.